KUALITAS BERITA PILKADA KOTA MALANG DI MEDIA DARING - Qorib, Fathul; Kariman, Kariman (Jurnal Komunikasi Nusantara, 2020)
The development of technology makes online media get a greater portion of readers than print media that were first born. Online media that rely on speed often violate journalistic code of ethics so it should be reviewed so that there is an improvement. This study aims to look at the quality of news on Regional Election (Pilkada) on Malangvoice.com. This study uses a qualitative method. The data source in this research are the news in Malangvoice.com online mass media related to Malang City Election News which was taken in June 2018. This media was chosen because it is one of the most widely read media in Malang Raya. The set of analysis units amounted to 15 Pilkada news in the voting month, namely June 2018. The news quality theory used in this study is in accordance with the Journalistic Code of Ethics, namely accuracy, balance, objectivity, concise, and actual. The results showed Malang Voice has advantages in the field of technical quality such as writing, the object of reporting, brevity and actuality. But Malang Voice has weaknesses in the quality of news content such as accuracy, objectivity and balance.